Generation Z’s Perceptions of Pancasila Education in Fostering Nationalism: A Study at Islamic Universities in Indonesia - Firmansyah, Firmansyah; Kuswandari, Yuli; Muqowim, Muqowim (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – The phenomenon of the degradation of the understanding of Pancasila by Generation Z needs to be followed up to foster a spirit of nationalism by internalizing the values of Pancasila. The researcher intends to determine Generation Z’s perception of the importance of Pancasila in realizing the spirit of nationalism in Islamic universities.Method – This study uses a qualitative descriptive approach implemented in the Islamic Religious Education study program of Sunan Kalijaga State Islamic University, Yogyakarta. The selection of research subjects was carried out using a purposive sampling technique, namely the selection of informants based on the criteria of relevance and experience of informants on the research topic. The data analysis technique in this study uses the Miles and Huberman model which includes three stages: data reduction, data presentation and drawing conclusions. Findings – The results of the study show that Pancasila Education has an important influence on Generation Z students. By internalizing the values of Pancasila, Generation Z is expected to have intellectual, emotional, social, and spiritual intelligence as well as a sense of love for the homeland and a responsible attitude that is able to play a role in community, national, and state life. Research Implications – This research needs to be conducted in order to foster a sense of nationalism for the young generation of Indonesian citizens through Pancasila and Citizenship education in elementary, middle, and college environments. Thus, the values of Pancasila and the spirit of nationalism will always be embedded in the souls of the young generation and their every behavior so that they will not be carried away by the current of globalization.